Changes in Circulating Metabolites During Weight Loss are Associated with Adiposity Improvement, and Body Weight and Adiposity Regain During Weight Loss Maintenance: The SATIN Study. Issue 17 (21st July 2021) - Papandreou, Christopher; García‐Gavilán, Jesús; Camacho‐Barcia, Lucía; Toft Hansen, Thea; Harrold, Joanne A.; Sjödin, Anders; Halford, Jason C. G.; Bulló, Mònica
Abstract : Scope: To examine the relationship between changes in circulating metabolites during diet‐induced weight loss and changes of adiposity. This study also investigates changes in these metabolites in relation to body weight and adiposity regain during a weight loss maintenance period. Methods and Results: This cohort study is nested within the Satiety Innovation (SATIN) study. Participants (n = 162) achieving ≥8% weight loss during an initial 8‐week low‐calorie formula diet (LCD) are included in a 12‐week weight loss maintenance period. A targeted metabolite profiling (123 metabolites) approach is applied using three different platforms (proton nuclear magnetic resonance, liquid chromatography mass spectrometry, gas chromatography mass spectrometry). Changes in several lipid species and citric acid are significantly associated with greater reduction of body weight, total fat, and abdominal adiposity distribution during the LCD. Decreases in the concentrations of lysophosphatidylcholines (LPCs) 14:0, LPC 20:3, phosphatidylcholine (PC) 32:2, PC 38:3, sphingomyelin (SM) 32:2, and increases in citric acid concentrations during the LCD are associated with adiposity regain and loss, respectively, during the weight loss maintenance period. Conclusions: The results show that weight loss is associated with changes in lipid species and citric acid. These changes are related to subsequent weight and adiposity regain identifying the adipose lipid metabolism as an important factor for the maintenance of lost weight and adiposity. Abstract : Achieving ≥8% weight loss during an initial 8‐week period is associated with decreases in the concentrations of specific lysophosphatidylcholines (LPC), phosphatidylcholine (PC), sphingomyelin (SM) species and increases in citric acid, which are related to adiposity regain and loss, respectively, after 12 weeks of weight loss maintenance.